Self-Efficacy dan Resiliensi: Sebuah Tinjauan Meta-Analisis - Cicilia Tanti Utami (Buletin Psikologi, 2017)
This article examined the correlation between self-efficacy and resilience with meta-analytic technique. The quanitative review includes 20 correlations from 15 studies. Two artifacts allow for correction in these study are sampling error and measurement error. Summary analysis provided support for the hypothesis that self-efficacy has a positive correlation to resilience. The result shows that the correlation of self-efficacy and resilience is 0.591, with the confidence level is 95%.